Temperature dependence of the magnetic field penetration depth in YBa₂Cu₃O₇-b: effect of impurity scattering - Golubov, A.A.; Trunin, M.R.; Zhukov, A.A.; Dolgov, O.V.; Shulga, S.V. (Физика низких температур, 1996)
Temperature dependence of the anisotropic magnetic field penetration depth of a two-band superconductor is calculated in the model of strong s-wave pairing interaction in one of the bands (S band) and induced superconductivity in the second band (N band). The results of the calculations are compared with experimental data on the (ab) plane and c axis penetration depth in YBa₂Cu₃O₇-b . It is shown that all recent measurements over the entire temperature range are consistent with the two-band model.